2018
DOI: 10.1002/ceat.201700091
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Study of Flow Induced by a Grooved High‐Shear Impeller in an Unbaffled Tank

Abstract: A detailed hydrodynamic characterization in the transitional flow regime of two variants of the Norstone Polyblade high-shear impeller (HSI), of industrial relevance, is presented. The study was carried out on a simulated Newtonian fluid using computational fluid dynamics (CFD). Measurements of power number were carried out to validate the simulation results. Hydrodynamic parameters considered of key importance in powder dispersion processes (i.e., viscous dissipation and effective circulation) were used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Regarding the ε̅ calculated from the experimental values of power and , it was found that simulations present lower values by 36.3 and 38.4% (mean 37.35%) at 300 and 500 rpm, respectively. Under-prediction of ε̅ using CFD has been reported in other studies, for example, using large eddy simulation and detached eddy simulation by 25 to 45%, which is compatible with the 37.35% average value obtained in this work. Based on the percentage of under-prediction obtained, the results of the hydrodynamic stress were corrected ( ), increasing the values of ε̅ by 37.35%. The volume-weighted average hydrodynamic stresses at 300 rpm are shown in Table .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the ε̅ calculated from the experimental values of power and , it was found that simulations present lower values by 36.3 and 38.4% (mean 37.35%) at 300 and 500 rpm, respectively. Under-prediction of ε̅ using CFD has been reported in other studies, for example, using large eddy simulation and detached eddy simulation by 25 to 45%, which is compatible with the 37.35% average value obtained in this work. Based on the percentage of under-prediction obtained, the results of the hydrodynamic stress were corrected ( ), increasing the values of ε̅ by 37.35%. The volume-weighted average hydrodynamic stresses at 300 rpm are shown in Table .…”
Section: Resultssupporting
confidence: 88%
“…It is important to point out that in other studies, shorter and longer experimental values of mixing times than the simulated values have been reported. It can be explained because the RANS models do not capture the transient turbulent structures due to the dampening effect . The experimental and CFD θ 95% results obtained are in good agreement.…”
Section: Resultsmentioning
confidence: 64%
“…From Eqs, (11), , (14) and (15), the Newtonian and non-Newtonian N P curves as a function of Re (or Re a ) can be obtained. For the laminar regime, N P is inversely proportional to Re, i.e.,…”
Section: Experimental and Numerical Calculation Of The Metzner-otto Cmentioning
confidence: 99%
“…It has been reported that the impeller-induced maximum values of shear, or viscous dissipation in the laminar regime, determines the ultimate particle size in solid-liquid dispersions [9,10]. In the laminar regime, maximum values of shear rate and its associated shear stress correspond with maximum values of viscous dissipation; therefore, these three hydrodynamic parameters are frequently related to the ultimate particle size in actual pigment dispersion processes [3,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Before titanium-dioxide powder can be used as a paint, its structure has to be broken into smaller parts. This process is performed in special devices such as ball mills [9,10] and high shear mixers [11,12]. Ultrasonication [5,13] and high-pressure nozzles [13][14][15][16] are often applied.…”
Section: Introductionmentioning
confidence: 99%